Late‐News Paper: Single Mirror Interferometric Display – A New Paradigm for Reflective Display Technologies. Issue 1 (June 2014) - Hong, John; Chan, Edward; Chang, Tallis; Fung, Richard; Kim, Cheonhong; Ma, Jian; Pan, Yaoling; Wen, Bing; Reines, Isak; Lee, Chong
Abstract A next‐generation technology iteration of Qualcomm's Mirasol displays, called the single mirror interferometric (SMI) display, is demonstrated. SMI features individual pixels whose reflectance properties can tune through a continuum of colors, including high contrast black and white reflectance states. The MEMS optical pixel is described, along with early system demonstrations.